PHOTOGRAPHY AS ANTI-MEMORY - Kangelaris, Fotis (Design/Arts/Culture, 2023)
It is widely known that photography is related to memory. The invention of photography was inextricably linked to memory, as a more effective and direct way than painting. A more effective and direct way to depict the object to be remembered such as the rulers’ portraits or the painted depictions of animals and plants that navigators met while discovering the world, always having a painter with them. However, in the present study, we attempt to show that the innermost reason for the invention and use of photography was never related to memory, and if it was related, the reason was to make us forget what we were aiming to remember. The inner cause of photography’s position in human history and art was: 1) To bring us into contact with the invisible: to that, photography is analysed through philosophy’s prism and especially as Romanticism’s offspring that attempts to go beyond reality and connect us with alterity and the invisible which dictates the visible. 2) To offer a sense of reality to the structural void on which the human psyche is composed: to that, photography is analysed through the prism of psychoanalysis as a symbolic mirror of the photographer’s and viewer’s psyche, a process based on the “mirror stage” (Lacan, 1966). 3) To make us forget: to that, photography is analysed through an anthropological regard where, via common mechanisms which are related to Magic, the photographer and the viewer have the potential to surpass reality’s flow through amnesia.